Analysis and design of a compact ultra-wideband antenna with WLAN and X-band satellite notch - Mohssine El Ouahabi; Aziz Dkiouak; Alia Zakriti; Mohamed Essaaidi; Hanae Elftouh (International Journal of Electrical and Computer Engineering (IJECE), 2020)
A compact design of ultra-wideband (UWB) antenna with dual band-notched characteristics based on split-ring resonators (SRR) are investigated in this paper. The wider impedance bandwidth (from 2.73 to 11.34 GHz) is obtained by using two symmetrical slits in the radiating patch and another slit in the partial ground plane. The dual band-notch rejection at WLAN and X-band downlink satellite communication system are obtained by inserting a modified U-strip on the radiating patch at 5.5 GHz and embedding a pair of rectangular SRRs on both sides of the microstrip feed line at 7.5 GHz, respectively. The proposed antenna is simulated and tested using CST MWS high frequency simulator and exhibits the advantages of compact size, simple design and each notched frequency band can be controlled independently by using the SRR geometrical parameters. Therefore, the parametric study is carried out to understand the mutual coupling between the dual band-notched elements. To validate simulation results of our design, a prototype is fabricated and good agreement is achieved between measurement and simulation. Furthermore, a radiation patterns, satisfactory gain, current distribution and VSWR result at the notched frequencies make the proposed antenna a suitable candidate for practical UWB applications.